2022
DOI: 10.31557/apjcp.2022.23.7.2477
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Distribution and Prevalence of High-Risk Human Papillomavirus Infection among Women in Samsun Province of Turkey

Abstract: Cervical cancer (CC), the fourth most frequently diagnosed cancer, is the fourth major death cause of women, showing an estimated 342,000 deaths and 604,000 new cases worldwide in 2020 (Sung et al.,2021). CC is increasing in number every year, and the patient population is getting younger. Thus, CC endangers women's life and health as a significant disease (Olusola et al., 2019). An essential step in human development and reproduction is to focus on women's health. We still focus on prevention at present due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In this study, the most common HR-HPV genotype was HPV16 (70%), followed by HPV31 (21.6%). The data we obtained were compatible with other studies carried out in Turkey [ 2 , 22 , 27 ]. If the immune system fails to clear the HR-HPV types, infections will be associated with a high risk for cervical disease progression leading to cervical cancer [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, the most common HR-HPV genotype was HPV16 (70%), followed by HPV31 (21.6%). The data we obtained were compatible with other studies carried out in Turkey [ 2 , 22 , 27 ]. If the immune system fails to clear the HR-HPV types, infections will be associated with a high risk for cervical disease progression leading to cervical cancer [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…The leading cause of cervical cancer has been revealed to be human papillomavirus (HPV) infection, which has led to the recognition of CC as a malignancy with a preventable and treatable etiology. Currently, most countries support the prompt deployment of CC screening, using a thorough strategy that includes cervical cytology and HPV testing [ 2 ]. An increasing amount of evidence suggests that HPV vaccinations may significantly reduce the prevalence of HPV infections.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a study in South Korea, comprising 18,170 women had a HR-HPV positive rate of 12.5% (Ouh et al, 2018). Similarly, a study in Turkey showed that the incidence rate of HR-HPV infection was ∼9.17% (Taskin et al, 2022). Meanwhile, in countries with relatively underdeveloped economies, such as sub-Sahara Africa and Bangladesh, the HR-HPV infection rate was 34% (Seyoum et al, 2022) and ∼41.86% (Sharmin et al, 2021), respectively.…”
Section: Discussionmentioning
confidence: 98%